LONG-ACTING ERYTHROPOETIN EFFICACY IN THE TREATMENT OF NEPHROGENIC ANEMIA IN PATIENTS WITH CHRONIC KIDNEY DISEASE AT A PREDIALYSIS STAGE - Yu S Milovanov (Терапевтический архив, 2012)
Aim. Comparison of efficacy of 12-month treatment of anemia in patients with chronic kidney disease (CKD) of stage III — IV with a long-acting drug darbepoetin alpha — aranesp and short-acting drug erythropoietin beta — recormon. Material and methods. A total of 44 patients with CKD of stage III-IV were divided into two groups. Of them, 24 had chronic glomerulonephritis and 20 had tubulointerstitial nephritis with verified nephrogenic anemia. Group 1 consisted of 22 patients given long-acting erythropoetin (darbepoetin alpha) in an initial dose 0,75 mcg/kg each 2 weeks subcutaneously. Group 2 consisted of 22 patients matched by age, gender, severity of anemia and renal failure with group 1 patients given short-acting erythropoietin (erythropoietin beta) in an initial 20 IU 3 times a week subcutaneously for 12 months. In the phase of anemia correction and supporting therapy, the levels of packed red blood cells, Hb, free serum ferrum, ferritin, percentage of iron in transferrin, serum albumin in blood serum, creatinin, glomerular filtration rate were examined monthly. The patients themselves daily measured blood pressure, diuresis, body mass. Results. The target level of Hb 110-120 g/l was achieved faster in group 2 than in group 1 (3 and 4 months, respectively), p < 0.05). In the phase of supporting a target Hb level, on the opposite, darbepoetin alpha provided more stable hemopoetin effect than erythropoietin beta, darbepoetin alpha median dose being constant in the course of the study.